Religion and military service (social and philosophical analysis of the relationship) - Semenov, S. S.; Gegechkorі О. V.; Zhelago А. М. (Honor and Law, 2019)
On the basis of socio-philosophical analysis analyzed the problem of the relationship between religious and military structures in order to optimize the practical behavior of the believer at the time of the commission of armed violence.